Nematode Fauna Associated with Kiwi (Actinidia delicosa, Chev.) Plants in Machchhegaun, Kathmandu, Nepal - Chhetri, Bijay (Nepal Journal of Biotechnology, 2019)
Plants harbor many trophic groups of nematodes in them. The plant production is also determined by the occurrence of nematodes adjacent to the rhizosphere of plants, such as parasitic, free-living etc. Altogether 40 samples from the 30 cm away from the Kiwi plants were examined to detect the nematode distribution in Kiwi plants in Machchhegaun, Kathmandu, Nepal. Total 10 genera of nematodes including both free living/beneficial and parasitic were identified. Overall, 880 individuals of 10 nematodes genera belonging to four orders were found to be linked with Kiwi plants, among them the highest report was of order Dorylaimida (40.91%) (Dorylaimus spp., Cephalobus spp., Eucephalobus spp. and Discolaimus spp.) which was followed by Mononchida (36.36%) (Iotonchus spp., Parahadronchus spp. and Mononchus spp.), Rhabditida (18.18%) (Rhabditis spp. and Mesorhabditis spp.) and Tylenchida (4.55%) (Helicotylenchus spp.). No any published data about study of plant nematodes was found from study area. So, these four order of plant nematodes have been reported for the first time associated with Kiwi plants from Machchhegaun in Nepal. The result specified no significant distribution of nematodes in all Kiwi plants. Proper management of manures and Kiwi plants treatment is recommended for more production of Kiwi fruits in study area by nitrogen reduction, phosphorus reduction, odor reduction, energy recovery and adding value to manure techniques.